Evidence for Possible Biological Advantages of the Newly Emerging HIV-1 Circulating Recombinant Form from Malaysia - CRF33_01B in Comparison to its Progenitors _ CRF01_AE and Subtype B - Lau, Katherine A.; Wang, Bin; Miranda-Saksena, Monica; Boadle, Ross; Kamarulzaman, Adeeba; Ng, Kee Peng; Saksena, Nitin K. (Bentham Science Publishers, 2010)
In Malaysia, co-circulation of CRF01_AE and subtype B has resulted in the emergence of the second generation derivative; CRF33_01B in approximately 20% of its HIV-1 infected individuals. Our objective was to identify possible biological advantages that CRF33_01B possesses over its progenitors. Biological and molecular comparisons of CRF33_01B against its parental subtypes clearly show that CRF33_01B replicated better in activated whole peripheral blood mononuclear cells (PBMCs) and CD4+ T-lymphocytes, but not monocyte-derived macrophages (MDMs). Also, its acquired fitness was greater than CRF01_AE but not subtype B. Moreover, CRF33_01B has higher rate of apoptotic cell death and syncytia induction compared to subtype B. These adaptive and survival abilities could have been acquired by CRF33_01B due to the incorporation of subtype B fragments into the gag-RT region of its full-length genome. Our studies confirm the previously held belief that HIV-1 strains may harbor enhanced biological fitness upon recombination. We therefore estimate a possible gradual replacement of the current predominance of CRF01_AE, as well as wider dissemination of CRF33_01B, together with the identification of other new CRF01_AE/B inter-subtype recombinants in Malaysia.